The effect of small games on reducing shyness among primary school students 9-10 years old (Journal of the College of Basic Education, 2022)
The study aimed to identify the effect of small games in reducing shyness among primary school students aged 9-10 years.The researcher used the experimental approach for its suitability to the formula and objectives of the study, by designing equal groups, experimental and controlThe sample consisted of (24) primary school pupils, whose ages ranged from (9-10) years, who suffer from shyness in a remarkable way, and they were chosen in a deliberate manner after they were appointed by the guiding teacher. 12) for the experimental group. The study concluded that all games, in general, have a primary role in creating an atmosphere of fun, excitement, and suspense that gives the child an opportunity to express himself, form his personality with his colleagues, and get rid of the fear and shyness that afflicts his personality.